Adaptation of Working Culture in Police Culture in Pandemic Times - Ayi Satria Yuddha; Vita Mayastinasari; Andy Hermawan; Muhammad Mustofa (Budapest International Research and Critics University, 2022)
The COVID-19 pandemic through the spread of the SARS-CoV-2 virus since approximately two years ago, perhaps these two fields have never been directly related. Currently, the police and health are closely related. The spread of the epidemic in the community inevitably affects how the police adapt in carrying out their duties, functions, and roles. This pandemic has changed the social order system, including the work culture. The methodology used is by using a qualitative approach. On the other hand, the pandemic situation has created challenges in adapting to the working culture within the police organization. How police officers are able to adapt their work culture to the emergency situation of the pandemic. learning organization where organizational performance will increase supported by individual performance starting from the support of organizational commitment, organizational culture and leadership. With regard to working culture during the pandemic, leaders are at the forefront of bringing about change and need support from subordinates.